2003
DOI: 10.1046/j.1365-313x.2003.01773.x
|View full text |Cite
|
Sign up to set email alerts
|

Loss of actin cytoskeletal function and EDS1 activity, in combination, severely compromises non‐host resistance in Arabidopsis against wheat powdery mildew

Abstract: SummaryPlant immunity against the majority of the microbial pathogens is conveyed by a phenomenon known as non-host resistance (NHR). This defence mechanism affords durable protection to plant species against given species of phytopathogens. We investigated the genetic basis of NHR in Arabidopsis against the wheat powdery mildew fungus Blumeria graminis f. sp. tritici (Bgt). Both primary and appressorial germ tubes were produced from individual Bgt conidia on the surface of the Arabidopsis leaves. Attempted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
166
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(171 citation statements)
references
References 55 publications
4
166
1
Order By: Relevance
“…In addition to the deposition of cell wall reinforcements and focal accumulation of penetration-related proteins such as PEN3, the accretion of cytoplasm and organelles at sites of attempted fungal penetration involves reorganization of actin cytoskeleton, which forms a radial array focused on penetration site (10,11,(14)(15)(16)(17)(18). Consistent with this finding, disruption of AFs hampers penetration resistance, leading to increased penetration frequency by various fungal and oomycete pathogens (15)(16)(17)19). However, the mechanisms that drive AF dynamics and active transport of cellular components toward sites of attempted pathogen penetration remain elusive.…”
mentioning
confidence: 67%
“…In addition to the deposition of cell wall reinforcements and focal accumulation of penetration-related proteins such as PEN3, the accretion of cytoplasm and organelles at sites of attempted fungal penetration involves reorganization of actin cytoskeleton, which forms a radial array focused on penetration site (10,11,(14)(15)(16)(17)(18). Consistent with this finding, disruption of AFs hampers penetration resistance, leading to increased penetration frequency by various fungal and oomycete pathogens (15)(16)(17)19). However, the mechanisms that drive AF dynamics and active transport of cellular components toward sites of attempted pathogen penetration remain elusive.…”
mentioning
confidence: 67%
“…Although until recently little was known about the biochemical defenses that contribute to nonhost resistance, cytological descriptions suggested that a majority of inappropriate fungal pathogens were unable to breach the plant cell wall and infiltrate host cells (Yun et al, 2003;Zimmerli et al, 2004). However, some variation in penetration efficiency exists among different host and fungal pathogen combinations (Mellersh and Heath, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…These studies also showed that plants respond actively to attack by inappropriate pathogens and do not rely solely on preformed and constitutive barriers for protection against inappropriate pathogens (Meyer and Heath, 1988;Zimmerli et al, 2004). Furthermore, it appears that operationally, nonhost resistance can be divided into penetration resistance, barriers limiting entry of the pathogen into cells, and postpenetration resistance, mechanisms that act intracellularly if penetration resistance is overcome (Fernandez and Heath, 1991;Huitema et al, 2003;Mellersh and Heath, 2003;Yun et al, 2003;Zimmerli et al, 2004;Lipka et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be generally classified into preformed and induced defence mechanisms. Preformed defence mechanisms include formation of plant cytoskeleton and barriers against pathogenic invasion (Kobayashi et al 1997;Yun et al 2003), and constitutive accumulation of a variety of secondary metabolites, especially those with antimicrobial activity (Osbourn 1996). Induced defence mechanisms comprise of accumulation of components involved in preformed defence mechanisms, activation of plant defence signalling, accumulation of reactive oxygen species and initiation of hypersensitive response (HR) in some cases (Kamoun et al 1999;Heath 2000;Lauge et al 2000;Mellersh et al 2002;Mellersh and Heath 2003;Christopher-Kozjan and Heath 2003;Shimizu et al 2003;Mysore and Ryu 2004).…”
Section: Introductionmentioning
confidence: 99%